Borna disease virus (BDV) circulating immunocomplex positivity in addicted patients in the Czech Republic: a prospective cohort analysis - Rackova, Sylva; Janu, Lubos; Kabickova, Hana (BMC psychiatry, 2010)
BACKGROUND: Borna disease virus (BDV) is an RNA virus belonging to the family Bornaviridae. Borna disease virus is a neurotropic virus that causes changes in mood, behaviour and cognition. BDV causes persistent infection of the central nervous system. Immune changes lead to activation of infection. Alcohol and drug dependence are associated with immune impairment. METHODS: We examined the seropositivity of BDV circulating immunocomplexes (CIC) in patients with alcohol and drug dependence and healthy individuals (blood donors). We examined 41 addicted patients for the presence of BDV CIC in the serum by ELISA at the beginning of detoxification, and after eight weeks of abstinence. This is the first such study performed in patients with alcohol and drug dependence. RESULTS: BDV CIC positivity was detected in 36.59% of addicted patients on day 0 and in 42.86% on day 56. The control group was 37.3% positive. However, we did not detect higher BDV CIC positivity in addicted patients in comparison with blood donors (p = 0.179). The significantly higher level of BDV CIC was associated with lower levels of GGT (gamma glutamyl transferase) (p = 0.027) and approached statistical significance with the lower age of addicted patients (p = 0.064). We did not find any association between BDV CIC positivity and other anamnestic and demographic characteristics. CONCLUSIONS: In our study addicted patients did not have significantly higher levels of BDV CIC than the control group. The highest levels of BDV CIC were detected in patients with lower levels of GGT and a lower age. TRIAL REGISTRATION: This study was approved by the ethical committee of the University Hospital Medical Faculty of Charles University in Pilsen, Czech Republic (registration number 303/2001).
Keywords: senioři; Alcoholism; Borna disease virus; Blood Donors; Česká republika; Cohort Studies; bornaská nemoc; Middle Aged; Antigen-Antibody Complex; mužské pohlaví; Antibodies, Viral; Prospective Studies; Adult; Czech Republic; imunokomplex; kohortové studie; věkové faktory; alkoholismus; Antigens, Viral; Substance-Related Disorders; ženské pohlaví; poruchy spojené s užíváním psychoaktivních látek; návykové chování; prospektivní studie; Behavior, Addictive; Humans; lidé středního věku; protilátky virové; Age Factors; antigeny virové; dospělí; dárci krve; virus bornaské nemoci; Aged; Female; Borna Disease; lidé; Male